The The Use of English in Promoting Fashion - Desi Andriani (International Journal of English and Applied Linguistics (IJEAL), 2021)
This research is conducted to know the use of English in promoting fashion in social media. In social media, many people upgrade their style to sell. They sometimes used English to advertise to attract readers' attention to buy. The research aims to know the use of English in terms of the meaning of language and word order of the English used in promoting fashion. This research is a kind of descriptive research. The researcher took the data from sellers' posts on social media. The data were analyzed based on two variables. They are grammar and word order. The research results showed that the English used to promote fashion is incorrect and does not follow the correct word order and grammar.